PENGARUH PENANAMAN MODAL ASING TERHADAP PENYERAPAN TENAGA KERJA DAN PDRB PROVINSI JAWA BARAT MENGGUNAKAN PANEL DINAMIS - Mawarni, Diana; Tiara Nirmala; Imam Awaluddin (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
This research aims to analyze the impact of foreign direct investment (FDI) in the manufacturing sector on labor absorption and Gross Regional Domestic Product (GRDP) in West Java Province. Specifically, this research examines the effect of FDI, real wages, real interest rates, and GRDP on labor absorption, as well as the effect of FDI, domestic investment, capital expenditure, and labor on GRDP. The data used is panel data from 2015 to 2023, analyzed with a dynamic panel. The results show that FDI has a positive effect on labor absorption and GRDP. All independent variables in both models are also proven to have a significant effect, both partially and jointly, on the dependent variable of labor absorption and GRDP.